Destruction of rocks by the non-explosive depleting compounds during mining - Sakhno, S.; Kobyliansky, i В.; Sakhno, I. (Розробка родовищ, 2016)
Purpose. Justification of the possibility of non-explosive coherent rocks destruction while carrying out stratal underground mine workings on the basis of the set of dependencies describing changes in physical and mechanical properties of the non-explosive depleting compounds (NDC) during hydration process in the blast-hole charges in relation to crack growth in the adjacent area. Methods. By conducting experiments on the unequal component triaxial compression unit, we obtained the dependence of changes in the physical and mechanical properties of the NDC on the hydration time and the relationships between the physical and mechanical properties. The required distance between the blast-holes with NDC was established analytically for non-explosive destruction by quasi-static pressure of the compound expansion. Findings. The study allowed to obtain empirical dependences of medium stress change, coefficient of transverse strain, strain modulus of the NDC for compound expansion in time. The dependence of the strain modulus of the NDC on medium stress has been established. The research resulted in the analytical dependence of the length of the crack progressing from the blast-hole walls into the massif depth while implementing non-explosive technologies of destruction on the compound expansion pressure, its elastic constants as well as physical and mechanical characteristics of the medium under destruction. Originality. Medium stresses caused by the NDC expansion grow in time similarly to the growth of the stress tensor components, the dependence of the strain modulus on average stresses being satisfactorily described by an exponential dependence. Practical implications. The results of experimental and theoretical studies, taking into account sufficient accuracy for practical applications, can be used to determine parameters of the quasi-static rocks breaking by non-explosive compound during stratal mining.